Perubahan Produktivitas Mahasiswa Selama Pandemi Covid-19 - Kammawati, Ayu; Subekti, Novendra Priyo; Yusida, Ermita; Prastiwi, Lustina Fajar (Journal of Technopreneurship on Economics and Business Review, 2020)
This study aims to analyze student activities, especially in the fields of education and economics during the Covid-19 pandemic. There are several aspects taken, namely seeing from the perspective of student income that has changed, so that it makes students more productive by starting entrepreneurship during a pandemic. The method in this research is descriptive quantitative with primary data sources. The results of this study indicate that most students in Indonesia, especially in the Malang region, have experienced a decline in income and have opened new businesses or started entrepreneurship during the Covid-19 pandemic, with various policies that have been made by the Government related to the Covid-19 pandemic. This has made changes in student productivity during the Covid-19 pandemic even more useful.